BUSANA BANGSAWAN DAN PENDETA WANITA PADA MASA MAJAPAHIT: KAJIAN BERDASARKAN RELIEF-RELIEF CANDI - Hari Lelono (BRIN, 1999)
In this paper, we will study the reliefs of temples in East Java, where the temples were built during the reign of the Majapahit Empire. The reliefs depicted contain elements of stories that were popular at that time, for example the stories of Sri Tanjung, Panji, Bubuksah and Gagangaking, and Jarum Atat. In addition to the reliefs of these temples, the ancient Javanese inscriptions mentioned the types of batik cloth used by the people at that time. In East Java, two reliefs of the temple were successfully constructed, namely; Pendopo Penataran temples in the eleventh - eighth centuries and the sixteenth - sixteenth century Kendalisodo temple. In the two temples, the reliefs of women are depicted wearing different clothes, both in terms of shape and how to wear them.